Pengembangan Aplikasi Media Pembelajaran Matematika Berbasis Android untuk Siswa Kelas V di SD Negeri 3 Panggisari Menggunakan Metode MDLC - Sholakhudin Al Ayubi; Sigit Sugiyanto (Jurnal Teknologi Informasi dan Multimedia, 2026)
This study aims to develop Android-based mathematics learning media for 5th-grade students of SD 3 Panggisari as a solution to the low interest in learning and the limitations of conventional learning media. The development method used is the Multimedia Development Life Cycle (MDLC) which includes the stages of concept, design, material collection, assembly, testing, and distribution. The application is designed to contain mathematics materials according to the cur-riculum, equipped with visual illustrations, practice questions, and multiple-choice-based evalu-ations. Functional testing using the black box method shows that all application features run well. The implementation results show an increase in student learning interest, indicated by the results of the questionnaire testing using a Likert scale which obtained an average value of 4.39, thus in-cluded in the agree category. With these results, this Android-based mathematics learning media can be accepted in elementary school environments and is suitable for use as a learning support medium.